2022
DOI: 10.3389/fmolb.2021.770729
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Prognostic Value of the PLOD Gene Family in Lung Adenocarcinoma

Abstract: Accumulating evidence has implicated members of the procollagen-lysine, 2-oxoglutarate 5-dioxygenase (PLOD) gene family, PLOD1, PLOD2, and PLOD3, in cancer progression and metastasis. However, their expression, prognostic value, and mechanisms underlying their roles in lung adenocarcinoma (LUAD) have not yet been reported. We downloaded PLOD data for LUAD and normal tissues from The Cancer Genome Atlas (TCGA). PLOD1-3 protein expression was evaluated using the Clinical Proteomics Tumor Analysis Consortium and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
(45 reference statements)
1
2
0
Order By: Relevance
“…In our study, LUAD patients with high FUT1 expression exhibited a better prognosis. Studies have validated that C1GALT1 [ 12 ], GALNT2 [ 13 ], PYGB [ 14 , 15 ], and PLOD2 [ 16 , 17 ] are associated with a poorer prognosis in LUAD, aligning with our conclusions. Presently, there are limited studies on POMK, with only one speculating on its potential cancer-promoting effect [ 18 ], and no relevant study in LUAD.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, LUAD patients with high FUT1 expression exhibited a better prognosis. Studies have validated that C1GALT1 [ 12 ], GALNT2 [ 13 ], PYGB [ 14 , 15 ], and PLOD2 [ 16 , 17 ] are associated with a poorer prognosis in LUAD, aligning with our conclusions. Presently, there are limited studies on POMK, with only one speculating on its potential cancer-promoting effect [ 18 ], and no relevant study in LUAD.…”
Section: Discussionsupporting
confidence: 90%
“…showed that the PLOD family members can be novel biomarkers for predicting LUAD prognosis (Meng et al, 2021). Being a member of the first membrane matrix metalloproteinases (MMPS), MMP14 has been shown to promote extracellular matrix (ECM) degradation to accelerate tumor cell migration, inflammation, invasion, angiogenesis and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, overexpression of PLOD3 could lead to poor prognosis in tumors such as gastric cancer, colon adenocarcinoma, and glioma [62][63][64][65]. Some studies have suggested that the PLOD family and its members could regulate the immune infiltration in some tumors such as gastric cancer, pancreatic cancer, lung adenocarcinoma, and low-grade glioma [30,[66][67][68][69].…”
Section: Introductionmentioning
confidence: 99%